2017
DOI: 10.1002/humu.23225
|View full text |Cite
|
Sign up to set email alerts
|

Lessons from the CAGI‐4 Hopkins clinical panel challenge

Abstract: The CAGI-4 Hopkins clinical panel challenge was an attempt to assess state-of-the-art methods for clinical phenotype prediction from DNA sequence. Participants were provided with exonic sequences of 83 genes for 106 patients from the Johns Hopkins DNA Diagnostic Laboratory. Five groups participated in the challenge, predicting both the probability that each patient had each of the 14 possible classes of disease, as well as one or more causal variants. In cases where the Hopkins laboratory reported a variant, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 33 publications
0
9
0
Order By: Relevance
“…In addition, Figure and Table S3 show the ROC curves and performance measures, respectively, for all submissions in each phenotype. Since the overall predictions are far from a perfect performance, the prediction assessment for each phenotypic trait was performed also in the group of patients where the Padua NDD lab noted a potentially causative variants like previous CAGI challenge assessments (data not shown; Chandonia et al, ). However, this did not show any improvement of predictor performance.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, Figure and Table S3 show the ROC curves and performance measures, respectively, for all submissions in each phenotype. Since the overall predictions are far from a perfect performance, the prediction assessment for each phenotypic trait was performed also in the group of patients where the Padua NDD lab noted a potentially causative variants like previous CAGI challenge assessments (data not shown; Chandonia et al, ). However, this did not show any improvement of predictor performance.…”
Section: Resultsmentioning
confidence: 99%
“…We have described the assessment of the CAGI‐5 ID challenge. This challenge is based on the phenotype evaluation of patients using gene panel sequences, in analogy to the CAGI‐4 Hopkins panel challenge (Chandonia et al, ). Where the Hopkins panel was testing for different monogenic diseases with Mendelian inheritance, the ID challenge focuses on complex disorders.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2019, we proposed a new computing experiment, focusing on the prediction of the variation of the free energy change induced by hFXN missense variants [ 85 ]. The assessment of the predictions submitted for the hFXN, and other challenges focusing on clinical applications, confirmed that the state-of-the-art methods for predicting the variation of protein stability change upon mutation are achieving a good level of performance, while methods for predicting pathogenic variants reached a good level of performance on challenges focusing on possible clinical applications [ 134 , 135 , 136 ]. The global effects of missense mutations on proteins can be highlighted from the analysis of the thermodynamic parameters of stability, distinguishing neutral mutations from destabilizing or stabilizing ones.…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 94%
“…At the level of full exome and genome sequence, there are challenges that assess methods for assigning complex traits phenotypes and that evaluate the ability to associate genome sequence and an extensive profile of phenotypic traits (including Cai et al., 2017; Daneshjou et al., ; Daneshjou et al., ; Giollo et al., ; Laksshman, Bhat, Viswanath, & Li, ; Pal, Kundu, Yin, & Moult, ; Wang et al., ). CAGI has also included challenges in which participants were asked to identify causative variants for rare diseases in gene panel, exome, and whole‐genome sequence data (including Chandonia et al., ; Kundu, Pal, Yin, & Moult, ; Pal, Kundu, Yin, & Moult, ). Many challenges have focused on cancer, given its prevalence and the impact of genetics.…”
mentioning
confidence: 99%